Changes in Alcohol Consumption and Determinants of Excessive Drinking During the COVID-19 Lockdown in the Slovak Republic - Gavurova, Beata; Khouri, Samer; Ivankova, Viera; Kubak, Matus (Frontiers in Public Health, 2022)
As a result of the coronavirus disease 2019 (COVID-19) pandemic, countries have been forced to adopt strong restrictions, such as lockdown, which can lead to serious consequences for public health, including the problematic use of addictive substances. The aim of this cross-sectional study was to examine changes in alcohol consumption and to identify determinants against the background of excessive drinking during the COVID-19 lockdown in the Slovak Republic. The research included 445 respondents (33% males and 67% females), and the data collection through the questionnaire took place from April 29, 2020 to July 1, 2020. Measures such as drinking frequency, amount of alcohol and excessive drinking were used to examine alcohol consumption. Descriptive analysis and binary logistic regression were used to meet the main aim. The findings provide a closer look at the situation in the Slovak Republic and contribute to comprehensive international knowledge. The frequency of excessive drinking did not change in about half of respondents (53% of males and 69% of females). More respondents decreased their excessive drinking than increased, both among males (31 and 16%, respectively) and females (25 and 6%, respectively). Similar results were found for drinking frequency and amount of alcohol. Amongst Slovak respondents, an increase in excessive drinking was more common among males, younger people, smokers, and smokers who increased smoking during the lockdown. Especially in the case of vulnerable populations, public policies should consider a response to impending problems. The findings of this study encourage the implementation of effective and evidence-based prevention programs, which are more than necessary in the Slovak Republic.